A Dual Color Immunohistochemistry Assay for Measurement of Cereblon in Multiple Myeloma Patient Samples. Issue 10 (November 2016) - Ren, Yan; Wang, Maria; Couto, Suzana; Hansel, Donna E.; Miller, Karen; Lopez-Girona, Antonia; Bjorklund, Chad C.; Gandhi, Anita K.; Thakurta, Anjan; Chopra, Rajesh; Breider, Michael
Abstract : Clinical interest in the measurement of Cereblon (CRBN), the primary target of the IMiDs immunomodulatory drugs lenalidomide and pomalidomide, has been fueled by its essential requirement for antitumor or immunomodulatory activity of both drugs in multiple myeloma (MM). However, limited analyses of clinical samples for CRBN gene expression or protein levels have utilized unvalidated reagents and assays, raising uncertainty about the interpretation of these results. We previously described a highly specific rabbit monoclonal antibody CRBN65 against 65-76 AA of human Cereblon. Here we describe a validated dual color bright-field Cereblon/CD138 immunohistochemical (IHC) assay utilizing CRBN65 and a commercial mouse monoclonal CD138 antibody. Sensitivity and specificity of the assay was determined and assay precision was shown for both cytoplasmic and nuclear Cereblon in MM bone marrow samples with coefficient of variation values of 5% and 2%, respectively. The dual IHC assay was effective for detecting a continuous range of Cereblon levels in 22 MM patient bone marrow core biopsies and aspirate clots, as shown by average cytoplasmic H-scores ranging from 63 to 267 and nuclear H-scores ranging from 17 to 250. Interpathologist comparison of MM sample H-scores by 3 pathologists demonstrated good concordance ( R 2 =0.73). This dual assay demonstrated superior Cereblon IHC measurement in MM samples compared with the single IHC assay using a published commercial rabbit polyclonal Cereblon antibody and could be used to explore the potential utility of Cereblon as a biomarker in the clinic. Abstract : Supplemental Digital Content is available in the text.